SP’z Series New Insights on Urology and Urological Research Part I - Dr. Sanjay P. Dhangar (SP’z Series New Insights on Urology and Urological Research Part I, 2022)
The practice of Urology has undergone evolutionary changes in the last few decades’ right from clinical signs symptoms to the recent investigation Era of Evidence Based Medicine, but still importance of clinical examination and bed side teaching will never fade. This book is envisaged to provide a range of learning avenues to reinforce the concepts and reiterate the minute details in Urology. This book will be a good source for research topics unique to the Indian urology scenario unlike others which have higher western influences which are nearly impossible in the Indian scenario where affordability is a major factor in making treatment decisions.